A capacitação em EaD como forma de preservar o patrimônio documental arquivístico da Universidade Federal do Rio Grande - FURG - Schwarzbold, Karin Christine (2015)
The research focus of this dissertation is the use of Virtual Environments of Teaching and Learning (AVEA in Portuguese) in training employees aiming at preserving the Universidade Federal do Rio Grande FURG (FURG) documental heritage. We attempted to sensitize the Institution directors about the importance of creating a training course on Distance Education (EaD) model, to study the Moodle environment to develop the proposal of a Pilot Course on Archiving Concepts in the form of Distance Education (EaD), and to disseminate the notions of archiving as a means to preserve the institution memory. This research is considered an applied study for its nature and qualitative regarding the problem of study approach. It is necessary that the institutions understand the need to archive documents in a proper way and that they provide their employees the opportunity to take part in training courses with the view to preserve the institution memory. The course was built and taught by the researcher together with a worker from the IT area and, a professional Archivist with an extensive experience in Conservation and Restauration. It was also possible to create an exclusive class, to the course students, as a partnership with the Brazilian General Controller Office (CGU) to approach the topic Access to Information Law. Particularly in this study, the archival document memory preservation is covered because the course met the proposed objectives and, the students were able to perceive that the care with the documents begins at the very moment of its creation and not only when the document is ready to be stored in the Archive.